Numerical Simulation of Two Circular Cylinders Arranged In-line in a Narrow Channel with a Reynolds Number of 1.0x10^5 - Zulfikar; Banta Cut; Suheri (Fakultas Teknik Universitas Samudra, 2026)
The flow of fluid around the circular cylinder (bluff body) is a fundamental problem in engineering with a wide range of applications, such as in offshore buffer pipes and chimneys. A common phenomenon is the emergence of drag forces, elevator forces, and vortex shedding. This study aims to reduce drag and lift forces in the arrangement of two circular cylinders arranged in line in narrow channels. The variation in the distance between cylinders was tested at T/D = 2.0, 2.5, 3.0, and 4.0 ratios (cylinder diameter D = 25 mm). Reduction efforts are made by placing the disruptor body (d=4) at an angle (0°, 120°, 240°) around the perimeter of the array. Numerical simulation was performed using the 2D unsteady RANS method with Ansys Student Fluent® 2021 software and the turbulence model (K-ω SST) at Reynolds numbers (Re = 1.0x10⁵) in cross-sectional channels (H = 300 mm, L = 150 mm). The results showed that at the T/D = 4.0 ratio, the wake interaction between the two cylinders was no longer dominant. The addition of a disruptor body at an angle (0°, 120°, 240°) has also been shown to be very effective in reducing the drag coefficient (CD) of both cylinders. The CD value in cylinder 1 without a disruptor body is 0.762 and with a disruptor body reaches 1.148 (reduction: [percentage with disruptor body Cyl 1]), while in cylinder 2, CD without a disruptor body is 0.762 and with a disruptor body, it reaches 1.148 (reduction: [percentage with disruptor body Cyl 2]). There are contradictions in the results data. The reduced CD values (1.148 and 1.148) were actually higher than the CD values without the disruptor body of 0.762 and 0.762, although the text states that there is a reduction and that it is very effective.